Evaluasi Kebijakan Dinas Pemberdayaan Perempuan dan Perlindungan Anak Kabupaten Buol dalam Menanggulangi Pelecehan Seksual di Masyarakat - Satria Satria; Sofyan Sofyan; Ahmad Sondeng (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze and evaluate the policies implemented by the Office for the Empowerment of Women and Child Protection (DPPPA), the Social Service, and relevant law enforcement agencies in Buol Regency in addressing sexual harassment cases, particularly those occurring within family environments, such as by stepfathers, uncles, or grandfathers. Using a qualitative approach with a descriptive-evaluative design, data were collected through in-depth interviews, participatory observations, and document studies. The research subjects included agency personnel, law enforcement officers, community members, and victims who had received support services. Data analysis followed a descriptive qualitative method, involving data reduction, data presentation, triangulation, and member checking to ensure validity. The findings indicate that formal policies have been established, including Standard Operating Procedures (SOPs) for complaint handling and victim assistance, child rights socialization programs, and cross-sector coordination with law enforcement. These policies are effective in providing direct protection and support to victims, including psychological counseling, social rehabilitation, and legal advocacy. However, the study reveals that policy effectiveness in preventing new cases remains limited due to challenges such as insufficient human resources, geographic barriers, low community awareness, and social stigma toward victims. To enhance policy implementation and effectiveness, the study recommends increasing the number of field personnel, strengthening socialization and education programs, integrating case data across agencies, and providing advanced training for personnel in handling sensitive cases. Law enforcement agencies are encouraged to strengthen cooperation with relevant agencies and educate the public on legal aspects, while the community is urged to actively report cases and support child protection initiatives. Overall, these strategies aim to improve implementation, effectiveness, and sustainability of child protection policies in Buol Regency, ensuring that children, particularly those in vulnerable family environments, receive comprehensive protection against sexual harassment